Traitement judiciaire de la violence de genre et désobéissance civile. Une analyse du discours de légitimation dans l’« affaire Juana Rivas » (25 juillet-28 août 2017) - Saupin Catherine (Amnis)
On 25 July 2017 Juana Rivas publicly announced that she would not obey court orders by not presenting her children at the meeting point with their Italian father, whom she had left a year earlier and whom she accused of domestic violence, and then disappeared with the two children for four weeks. This article focuses on the arguments used to legitimise Juana Rivas' decision, and more specifically the use of the figure of civil disobedience. It examines the strategies employed based on an analysis of the protagonist's discourse, in the letters she made public, and the campaign of support for her launched by various feminist networks and left-wing activists during August 2017 on social networks (#JuanaEstaEnMiCasa) and in the online press. It shows how, in a context of negotiation of the State Pact against Gender Violence, calls for civil disobedience, relayed not by Juana Rivas, but by activist networks, fit into a traditional and innovative repertoire of action aimed at opening a debate on the judicial treatment of this violence and on the protection of children in cases of gender violence. This contribution thus highlights one of the strategies used by Spanish feminists to help energise mobilisation and advance their demand for feminist justice.